The Eldon House diaries : five women's views of the 19th century - Harris, Robin S. (Robin Sutton), 1919-2000; Harris, Terry G.; Knight, Charlotte Owen Harris, 1828-1854 (Publications of the Champlain Society. Ontario series, 1994)
Edited from the diaries of Charlotte Owen Harris, 1848-1854; Amelia Ryerse Harris, 1857-1882; Sophia Howard Ryerson Harris, 1860-1861; Mary Elizabeth Lucy Ronalds Harris, 1868-1895; Amelia Archange Harris, 1882.